Metastasis of prostate cancer to breast: a case report - Zhang, Sirui; Peng, Wenting; Cheng, Lin; Pei, Bei; Zhou, Xiaoli; Wang, Mengjie; Jiang, Ling; Lu, Chao; Xu, Lingyun (Frontiers in Oncology, 2025)
We describe a 68-year-old man who had prostate cancer (PCa) diagnosed with breast metastasis, presenting as a breast mass. Seven years ago, the patient had PCa with bone metastasis and had been systematically receiving endocrine therapy for prostate cancer and osteoprotective treatment since the diagnosis. In October 2023, the patient visited our hospital due to bilateral breast masses for four days. Enlarged supraclavicular lymph nodes were detected, while multiple solid space-occupying lesions were observed in bilateral mammary tissues, classified as Breast imaging reporting and data system (BI-RADS) 4C. Subsequently, he underwent lumpectomy and was diagnosed with metastatic prostatic acinar adenocarcinoma.